Avaliação dos parâmetros físico-químicos, microbiológicos e detecção de genes de resistência aos antimicrobianos de águas de granjas de suínos e de lagos de zoológico e metagenômica da água de granjas de suínos - Faria, Ana Carolina Silva de (2016)
Water is essential for animal performance and can interfere in various production processes, such as animal health. Antimicrobials are widely used in animal production and can be a threat to human and animal health. With that, research to detect the antibiotic resistance genes (ARGs) in aquatic environments is important to identify potential reservoirs resistant microorganisms The metagenomic assay is based on the genomic DNA molecules analysis from microbial populations in environmental samples, and has been proposed to be the most accurate technique to describe microbial communities present in a habitat. These studies in animal consumption water’s samples or zoos lakes are scarce. Therefore, the objective of this study was to evaluate the presence of resistance genes to antimicrobiaals, pig’s farm and zoo lakes water quality and bacterial diversity in pig’s farms waters. Water samples from eight pig farms and nine Zoo lake’s were collected. These were filtered by vacuum pump system and DNA extracted from the filters. The PCR was done for the resistance gene six classes of antimicrobial: sulfonamides (sul I and sul II), β-lactam (ampC, blaPSE I and blaZ), macrolides (ermA, ermB and ermC), meticilinas (mecA, femA and msrA), aminoglycosides (aac (6')-aph (2"), aph3’-III and ant(4’)-Ia) and tetracyclines [tet(K) and tet(M)]. DNA extracted from seven pigs farm water samples were sequenced and metagenomic analyzes conducted using MG-RAST server. All samples showed resistance genes at least three of the six antimicrobial’s classes tested. This indicates a profile of multidrug resistance in the water that may be related with the indiscriminate use of antibiotics. The genes sul I, sul II, blaPSE I, ermB and blaZ were detected in all samples. The aminoglycosides (aac (6')-aph (2"), aph3’-III and ant(4’)-Ia) were detected in 87.5% samples; and ermA, femA and ampC in 75%. There was no evidence between presence of resistance genes, microbiological and physicochemical evaluation; or between microbiological analysis (total and fecal coliforms) and amount of resistance genes. The zoo water also presented the multiresistance profile and turbidity due to the presence of contaminants. The most common genes were sulfonamides (sul I and sul II) which are present in all lakes and β-lactamics blaPSE I in 77,8% and ampC in 66,7%. The tet(K), tet(M) and ermC were not detected. There was the correlation between the number of Enterobacteriaceae and increased in resistance gene’s detection. DNA’s water extracted from seven farms were sequenced and it was made metagenomic analysis by MG-RAST server. The farms water showing a bacterial diversity distributed in twelve phyla with the most common being Unclassified from bacteria, Proteobacteria and Firmicutes. The phylum Unclassified from bacteria, more abundant, can be related to influences of human activities or because of 16S rDNA technique is sensitive to low-frequency species and restricted to known species. The water’s farms are within the acceptable for animal consumption. However, the antimicrobial resistance genes presence is high, which may have direct connection with irrigation using wastewater from the settling lagoons, associated with the indiscriminate use of antibiotics. The likely sources zoo Lakes contamination are urban sewage or wastewater from neighboring residences that increase the presence of coliforms and frequency of resistance genes, which can be a risk to life of wild animals in captivity. It was reported a bacterial diversity in the samples and unexpected results were detected, as the abundance of Unclassified from bacteria, that may be related by the anthropogenic action or by the technique is restricted to known species.